2019
DOI: 10.1016/j.exer.2019.107704
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of the extracellular matrix during corneal wound healing

Abstract: The extracellular matrix (ECM) confers transparency to the cornea because of the precise organization of collagen fibrils and a wide variety of proteoglycans. We monitored the corneal wound healing process after alkali burns in rabbits. We analyzed the location and expression of collagens and proteoglycans, the clinical impact, and the recovery of optical transparency. After the animals received both general and ocular topical anesthesia, the central cornea of the left eye was burned by placing an 8-mm diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 55 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…Lumican is a member of the class II small leucine‐rich repeat proteoglycans superfamily, which constitutes collagen fibrils in the extracellular matrix (ECM) [7]. Lumican is ubiquitously expressed in a variety of tissues, such as skin [8], liver [9], intervertebral discs [10], kidney [11], bone [12], cornea [7], heart [13], uterus, pancreas [14], intestine, placenta and articular cartilage [15]. Lumican plays a crucial role in the regulation of collagen fibrillogenesis [7] in several tissues, such as skin [8] and cornea [16].…”
mentioning
confidence: 99%
“…Lumican is a member of the class II small leucine‐rich repeat proteoglycans superfamily, which constitutes collagen fibrils in the extracellular matrix (ECM) [7]. Lumican is ubiquitously expressed in a variety of tissues, such as skin [8], liver [9], intervertebral discs [10], kidney [11], bone [12], cornea [7], heart [13], uterus, pancreas [14], intestine, placenta and articular cartilage [15]. Lumican plays a crucial role in the regulation of collagen fibrillogenesis [7] in several tissues, such as skin [8] and cornea [16].…”
mentioning
confidence: 99%
“…To assess the protein expression of classic fibrotic markers, frozen sections were immunostained for collagen III, FN-EDA (also termed cellular FN), and a-SMA, all key markers of scarring. 52,53 For collagen III, compared to UnWnd, Wnd-NTC demonstrated a 276.2-fold increase in collagen III immunostaining (p < 0.01), which was reduced by 71.7% (p < 0.05) with Wnd-US09. The comparison between UnWnd and Wnd-US09 was not significant (Figures 3A and 3D).…”
Section: Immunohistochemistry For Fibrotic Markersmentioning
confidence: 96%
“…4 ). 28 , 29 Collagen type III production is upregulated in corneal fibroblasts by TGFβ, 30 , 31 and it is a major collagen upregulated in the corneal stroma after both fibrotic and non-fibrotic injuries. 28 , 32 Galiacy et al 33 showed that matrix metalloproteinase 14 overexpression in the cornea with a recombinant adeno-associated virus-based vector after injury reduced corneal opacity and expression of collagen type III.…”
Section: Contributions Of Stromal Matrix Components To Transparencymentioning
confidence: 99%